The Implementation of Physical Education Learning during Covid-19 Pandemic at Islamic Elementary School - Anang Setiawan; Seni Oktriani; Ahmad Mulya (Universitas Pendidikan Indonesia, 2022)
This study aimed to determine and analyze the implementation of Physical Education, Sports, and Health subject learning process during Covid-19 pandemic in an Islamic Elementary School in Sukagumiwang District, Indramayu Regency, West Java province. This study used a quantitative descriptive research design employing a one shot case study approach using a survey method. The sampling technique used incidental sampling technique. The samples of this study were Physical Education teachers, 6th Grade students of an Islamic Elementary School, and parents of the students living in Sukagumiwang district. The samples included 234 people consisting of 7 Physical Education teachers, 161 students, and 66 parents. The instrument of this study was an online questionnaire, containing 15 questions, created in Google Form. The results showed that Physical Education learning during Covid-19 pandemic changed. It was previously carried out full face-to-face, then shifted into online and blended learning (online and face-to-face). Although some adjustments had been made to learning materials, monitoring, and assessment, there were still technical or non-technical difficulties which might put the effectiveness of Physical Education learning through the use of online media in doubt.